Економічний базис забезпечення конкурентоспроможності страхової компанії: методико-прикладні аспекти - Prystupa, Liudmyla (Dr. Viktor Koval, 2018)
Introduction. The management of economic base ingredients is sent to forming, development and realization of competitive edges and providing of high level of competitiveness of insurance company, that in a result will assist not only the increase of client base of insurers, development insurance to the sector but also bringing in of additional investment resources in a home economy. A necessity of providing of high level of competitiveness of domestic insurance companies is in the conditions of active євроінтергації with the use of economic instruments, and also the presence of insufficiently known and debatable questions stipulates actuality of realization of further researches. Aim and tasks. The aim of the article is research of methodical and practical aspects of economic base of providing of competitiveness of insurance company and ground of directions of improvement of administrative activity in this sphere. Research results. In the article methodical and practical aspects of economic base of providing of competitiveness of insurance company are investigational in a modern market environment. The attention was paid to the study of methodological aspects of evaluation of the level of competitiveness and competitive position of the insurer. Conducted evaluation of indexes of competitiveness from data of IC "Alfa-Garant", allowed to learn the state, dynamics and to define the key measures of increase of level of competitiveness of insurance company. On the basis of generalization of results of research of the methodical and practical aspects of economic base of providing of competitiveness of insurance company strategic, operating, financial, investment, innovative and analytical dominants, the totality of that could form a target for the formation of perspective plans of development, control of current situation, implementation of existent obligations. Conclusions. Providing of competitiveness of insurance company is possible on condition of system administrative work from a search and optimization of ways of her development. An important role in this process is fixed to analytical work, methods and the receptions of that are various enough, at the same time compatible and not always answer the features of activity of insurance organization that requires the improvement of methodical principles of analytical evaluation of competitiveness of insurance company. Basis of economic base of providing of competitiveness of insurance company are financial resources, the base aspects of management are conditioned that by the normatively-legal base of conduct of insurance business.